(a+3)(a+3)=0

Simple and best practice solution for (a+3)(a+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+3)(a+3)=0 equation:


Simplifying
(a + 3)(a + 3) = 0

Reorder the terms:
(3 + a)(a + 3) = 0

Reorder the terms:
(3 + a)(3 + a) = 0

Multiply (3 + a) * (3 + a)
(3(3 + a) + a(3 + a)) = 0
((3 * 3 + a * 3) + a(3 + a)) = 0
((9 + 3a) + a(3 + a)) = 0
(9 + 3a + (3 * a + a * a)) = 0
(9 + 3a + (3a + a2)) = 0

Combine like terms: 3a + 3a = 6a
(9 + 6a + a2) = 0

Solving
9 + 6a + a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(3 + a)(3 + a) = 0

Subproblem 1

Set the factor '(3 + a)' equal to zero and attempt to solve: Simplifying 3 + a = 0 Solving 3 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + a = 0 + -3 a = 0 + -3 Combine like terms: 0 + -3 = -3 a = -3 Simplifying a = -3

Subproblem 2

Set the factor '(3 + a)' equal to zero and attempt to solve: Simplifying 3 + a = 0 Solving 3 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + a = 0 + -3 a = 0 + -3 Combine like terms: 0 + -3 = -3 a = -3 Simplifying a = -3

Solution

a = {-3, -3}

See similar equations:

| 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 | | 12x/15x | | -(6-3*6)-5=-2*6-2*6+1solve | | X^7=x^4+65 | | .2(4z-10)=.8z-2 | | 1/5(4z-10=4/5z-2 | | (2-v)(2v-3)=0 | | -4(x-4)+5=6(x+4)+1 | | 2x+2X+x=940 | | 5(-6x+9)+7= | | 20x+10=60w | | 10x=5(6x-2) | | -6(5x+7)+9= | | 7(4x+3)=.5(8x+5) | | 4x=2(8+30) |

Equations solver categories